Contrasting Reduced Overshadowing and Blocking - Wheeler, Daniel S. (2007)
Preexposure of a cue without an outcome (X-) prior to compound pairings with the outcome (XZ→O) can reduce overshadowing of a target cue (Z). Moreover, pairing a cue with an outcome (X→O) before compound training can enhance its ability to compete with another cue (i.e., blocking). Four experiments were conducted in a conditioned bar-press suppression preparation with rats to determine whether spacing of the X- or X→O trials would differentially affect reduced overshadowing and blocking. Experiment 1a showed that reduced overshadowing was larger with massed trials than with spaced trials. Experiment 1b found that blocking was larger with spaced trials than with massed trials. Experiments 2a and 2b indicated that these effects of trial spacing were both mediated by the associative status of the context at test. The results are interpreted in the framework of contemporary learning theories.